Interaction Effect of Phosphorus and Zinc Fertilizer for Different Levels in Growth of Two Varieties of Wheat Plant - Al-Ashor, A. A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To find the effect of interaction of the two elements , phosphorus and zinc, in some of the characters of two varieties of wheat (Triticum aestivum Var. Intisar) (Triticum aestivum Var. Ipa 95), An experiment was conducted in pots in the green house of the Department of Biological Science. / College of Education (Ibn-Al-Hiatham), for the season 2007/2008 using three levels of Phosphorus (0, 400, 800, mg / pot) and four levels of zinc (0, 10, 15, 20 mg / pot).  The experiment showed that the effect of the interaction of phosphorus and zinc was positive which increased the values of the features studied (length of plant, relative growth rate, nitrogen content, concentration of phosphorus and concentration of zinc) in the two varieties of wheat at their low levels and decreased the values of the above characters at the levels of higher fertilization of both phosphorus and zinc.  The results showed also a comparison between the two varieties of wheat (Intisar and Ipa 95) in the values of their feature according to the addition of different levels of both elements.